2009
DOI: 10.4049/jimmunol.0900620
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR Alleles in Amyloid β-Peptide Autoimmunity: A Highly Immunogenic Role for the DRB1*1501 Allele

Abstract: Active amyloid ␤-peptide (A␤) immunization of patients with Alzheimer's disease (AD) caused meningoencephalitis in ϳ6% of immunized patients in a clinical trial. In addition, long-term studies of AD patients show varying degrees of A␤ Ab responses, which correlate with the extent of A␤ clearance from the brain. In this study, we examined the contribution of various HLA-DR alleles to these immune-response variations by assessing A␤ T cell reactivity, epitope specificity, and immunogenicity. Analysis of blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…Although Ab-specific CD4 + T cell responses in SJL/J, C57BL/6, and DBA/1 mice were each targeted to a unique epitope, located between residues 10 and 24, 16 and 30, and 10 and 27, respectively, CD4 + T cells proliferated in response to both Ab10-24 and Ab19-33 in CBA/J mice. In humans, differing levels of CD4 + T cell responses to Ab have been observed in PBMCs and were specific for various Ab-derived epitopes restricted to different HLA-DR alleles, with the DRB1*1501 allele being highly immunogenic (9,10). Altogether, these studies indicated that the MHC genotype is an important parameter modulating CD4 + T cell reactivity to Ab.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although Ab-specific CD4 + T cell responses in SJL/J, C57BL/6, and DBA/1 mice were each targeted to a unique epitope, located between residues 10 and 24, 16 and 30, and 10 and 27, respectively, CD4 + T cells proliferated in response to both Ab10-24 and Ab19-33 in CBA/J mice. In humans, differing levels of CD4 + T cell responses to Ab have been observed in PBMCs and were specific for various Ab-derived epitopes restricted to different HLA-DR alleles, with the DRB1*1501 allele being highly immunogenic (9,10). Altogether, these studies indicated that the MHC genotype is an important parameter modulating CD4 + T cell reactivity to Ab.…”
Section: Discussionmentioning
confidence: 92%
“…Differing levels of Ab-specific T cell responses have been observed in PBMCs of human subjects, and were specific for various Ab-derived epitopes restricted to distinct HLA-DR alleles (9,10). Similarly, distinct T cell epitopes have been identified in SJL (H-2 s haplotype) and C57BL/6 mice (H-2 b ), which differ significantly in their propensity to develop Ab-specific CD4 + T cell responses (11).…”
mentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43] Several studies showed that DRB1*15-positive individuals produce antibodies causing more complement and inflammation mediated damage than DRB1*15-negative individuals after the same trigger. 44 The DRB1*15 allele association with autoimmunity and with multiresponsiveness against RBC and HLA antigens is not considered to be the result of more efficient antigen presentation in general, but rather DRB1*15 is part of a susceptibility haplotype and a surrogate marker for certain cytokine profiles, such as IFN-c, TNF-a, and IL-17. 35,[44][45][46] Regarding DRB1*15 and alloimmunity, a significantly higher DR2 frequency in high anti-HLA responders (PRA > 50%) compared to HLA antibody-negative (nonresponding [PRA 5%]) dialysis patients (25 and 16%, respectively) has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…44 The DRB1*15 allele association with autoimmunity and with multiresponsiveness against RBC and HLA antigens is not considered to be the result of more efficient antigen presentation in general, but rather DRB1*15 is part of a susceptibility haplotype and a surrogate marker for certain cytokine profiles, such as IFN-c, TNF-a, and IL-17. 35,[44][45][46] Regarding DRB1*15 and alloimmunity, a significantly higher DR2 frequency in high anti-HLA responders (PRA > 50%) compared to HLA antibody-negative (nonresponding [PRA 5%]) dialysis patients (25 and 16%, respectively) has been previously reported. 47 Later studies confirmed this association in end-stage renal disease patients, only for DR2 in combination with HLA-A2 and -B44 and -B53 antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 10 years, Aβ immunotherapy has transitioned from preclinical studies to human studies, with at least 13 different trials stratified into passive antibody administration and active vaccination with Aβ. In the first vaccine trial, using AN1792Aβ, 6% of patients developed meningoencephalitis (164), likely because of increased Th1 cell responses to Aβ (165,166). Eight vaccinated patients died, and autopsy examinations revealed profound reductions in amyloid load; however, they exhibited severe dementia at the time of death, suggesting that vaccination may not be sufficient to stop ongoing neurodegenerative processes.…”
Section: Immune-directed Therapies For Neurodegenerative Diseasesmentioning
confidence: 99%